La dignità umana e la ricerca del suo fondamento. Considerazioni a margine dall’Enciclica “Fratelli tutti” - Agnese Varsalona (Warszawskie Studia Teologiczne)
In the encounter with the other, each person somehow perceives his or her inviolable dignity, the safeguarding and promotion of which is an indispensable condition for the realization of more fraternal and inclusive societies. In this direction it is necessary to search the foundation of this dignity, as affirmed by Pope Francis' Encyclical "Fratelli tutti.” Such a search cannot prescind from the concept of person, taken up in the theological reflection of the first centuries to say the newness of the God of Jesus, and only later used to tell who is the human being, whose creation in the image and likeness of God grounds his inalienable dignity. The denial of man's capacity for self-transcendence and the existence of an absolute foundation - imagined as totalitarian and repressing diversity – expose to the danger of manipulation of what is human and disintegration of the social tissue. Therefore, there emerges the need to revisit the concept of absoluteness in the light of the God of Jesus, who is a relationship of love, unity in the diversity of the three persons.